2006
DOI: 10.1152/jn.00970.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neuronal Damage After Ischemic Insults in Mice Lacking Kir6.2-Containing ATP-Sensitive K+Channels

Abstract: . Enhanced neuronal damage after ischemic insults in mice lacking Kir6.2-containing ATP-sensitive K ϩ channels. J Neurophysiol 95: 2590 -2601, 2006. First published December 14, 2005 doi:10.1152/jn.00970.2005. Adenosine triphosphate (ATP)-sensitive potassium (K ATP ) channels, incorporating Kir6.x and sulfonylurea receptor subunits, are weak inward rectifiers that are thought to play a role in neuronal protection from ischemic insults. However, the involvement of Kir6.2-containing K ATP channel in hippocampus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 79 publications
1
80
0
2
Order By: Relevance
“…During the initial phase of hypoxia and ischemia, energy failure reduces the ATP/ADP ratio, which activates neuronal K ATP channels, causing hyperpolarization of the neuronal cell membrane and suppression of neuronal activity (Figure 2). Similar to previous reports [88,95,129,130] , we reported that membrane hyperpolarization was induced during the first 5 min of ischemia in both hippocampal and cortical neurons [92,93] . Using Kir6.2 knockout mice, we further reported that hippocampal CA1 neurons that were deficient for Kir6.2 revealed rapid depolarization and increased neuronal activity in response to hypoxia.…”
Section: Wwwnaturecom/aps Sun Hs Et Alsupporting
confidence: 91%
See 3 more Smart Citations
“…During the initial phase of hypoxia and ischemia, energy failure reduces the ATP/ADP ratio, which activates neuronal K ATP channels, causing hyperpolarization of the neuronal cell membrane and suppression of neuronal activity (Figure 2). Similar to previous reports [88,95,129,130] , we reported that membrane hyperpolarization was induced during the first 5 min of ischemia in both hippocampal and cortical neurons [92,93] . Using Kir6.2 knockout mice, we further reported that hippocampal CA1 neurons that were deficient for Kir6.2 revealed rapid depolarization and increased neuronal activity in response to hypoxia.…”
Section: Wwwnaturecom/aps Sun Hs Et Alsupporting
confidence: 91%
“…Using Kir6.2 knockout mice, we further reported that hippocampal CA1 neurons that were deficient for Kir6.2 revealed rapid depolarization and increased neuronal activity in response to hypoxia. In contrast, neuronal suppression occurred in wild-type neurons under similar conditions [92] . Hypoxic hyperpolarization in wild-type hippocampal CA1 neurons could be prevented by the K ATP channel blocker tolbutamide.…”
Section: Wwwnaturecom/aps Sun Hs Et Almentioning
confidence: 88%
See 2 more Smart Citations
“…They were sectioned into 25 m free-floating slices in PBS using a Kryostat 1720 (Leica, Wetzler, Germany). Immunostaining was performed as described previously (Sun et al, 2006). In brief, sections were blocked using a 1% BSA, 3% goat serum, 0.3% Triton X-100 in PBS solution for 90 min and doubled labeled with rabbit anti-3-nitrotyrosine (1:50; Upstate Biotechnology) and mouse anti-neuronal-specific nuclear protein (NeuN; 1:100; Chemicon, Temecula, CA) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%